Determinants of culinary tourism development in Pomeranian Voivodeship - Przemysław Charzyński; Alicja Gonia; Zbigniew Podgórski; Agnieszka Anna Kruger (Kazimierz Wielki University, 2017)
Pomeranian cuisine is characterized in the paper, It is a region in Northern Poland whose culinary heritage has been partially forgotten in the communist period, and is now being rediscovered. Typical dishes of traditional and modern Kashubian and Kociewie cuisine were presented, that can be a motivation for tourists interested in discovering and tasting of the regional dishes to visit this region. Geographical, historical and cultural heritage of Pomerania are the primary determinants of the formation of culinary trails and organization of  interesting food related events, which enables the development of this type of tourism in the studied area.